Leaf structure and ultrastructure changes induced by heat stress and drought during seed fi lling in fi eld-grown soybean and their relationship with grain yield - Carrera, Constanza Soledad (2021)
Fil: Carrera, Constanza Soledad. Instituto Nacional de Tecnología Agropecuaria; Argentina.